Biocompatibility improvement of titanium implants by coating with hybrid materials synthesized by sol–gel technique. Issue 12 (26th February 2014) - Catauro, M.; Bollino, F.; Papale, F.
Abstract Organic–inorganic hybrid materials based on zirconia and polyethylene glycol (PEG) have been synthesized via sol–gel method in the present study. Those materials, still in the sol phase, have been used to coat a titanium grade 4 (Ti‐4) substrate to improve its biological properties. Dip‐coating technique has been used to obtain thin films. PEG, a biocompatible polymer, used as the organic phase, has been incorporated with different percentages in an inorganic zirconium‐based matrix. Those hybrids have been characterized by Fourier transform infrared spectroscopy (FTIR) to detect interactions between the two phases. The films have been examined using SEM to detect morphological changes with PEG percentages. The potential applications of the hybrid coatings in biomedical field have been evaluated by bioactivity and cytotoxicity tests. The coated titanium was immersed in simulated body fluid (SBF) for 21 days and the hydroxyapatite deposition on its surface was subsequently evaluated, as that feature can be used as an index of bone‐bonding capability. SEM equipped with energy dispersive spectrometer (EDS) was used to examine hydroxyapatite formation. NIH 3T3 mouse embryonic fibroblast cells were seeded on specimens to evaluate cells–materials interactions and cell vitality was inspected using WST‐8 Assay. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4473–4479, 2014.